Field monitoring and instrumentation in microtunnelling/pipe jacking: A review and future directions - Asad Wadood; Bryan A. McCabe; Brian B. Sheil (Underground Space)
The popularity of trenchless techniques as a means of utility pipeline installation in urban environments, specifically microtunnelling/pipe-jacking, has increased in recent years due to its minimally-disruptive nature and reduced carbon footprint in comparison to conventional open-cut excavation methods. The response of pipes during the jacking process is complex and is governed by several factors, including ground conditions, the amount and distribution of lubrication, pipe and annulus size, pipeline misalignments and jacking force eccentricity, among others. Design practice remains based on empirical equations and previous drives through similar geology, resulting in uncertainty in jacking force estimates, thereby restricting adoption of the technique. In order to improve our understanding of the pipe-jacking process, pipes incorporating sensors providing real-time measurements of earth pressures, pore water pressures, axial strains and hoop strains can be used; but the number of such studies reported in the literature is small and the potential of instrumentation on routine projects is largely untapped. Moreover, jacking pipe monitoring practice lags behind the state-of-the-art instrumentation techniques used for monitoring other geotechnical infrastructure. The purpose of this paper is to provide a thorough review of learnings from instrumented pipe-jacking case studies and other supporting research, as well as to propose potential solutions to research gaps in the current state of design practice and field monitoring of pipe jacking projects.